2014
DOI: 10.1111/ced.12536
|View full text |Cite
|
Sign up to set email alerts
|

TheTNFAIP3polymorphism rs610604 both associates with the risk of psoriasis vulgaris and affects the clinical severity

Abstract: SNP rs610604 in the TNFAIP3 locus is associated with the clinical severity of PV in a Chinese Han population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
(37 reference statements)
1
8
0
Order By: Relevance
“…Keratinocyte-specific deletion of A20 results in epidermal hyperproliferation and ectodermal defects, but skin infiltration of immune cells has not been observed (Lippens et al, 2011). Genome-wide association studies identified TNFAIP3/A20 as a susceptibility locus for psoriasis (Haase et al, 2015;Indhumathi et al, 2015;Li et al, 2014;Nair et al, 2009;and Zhang et al, 2015), and its role as a negative regulator in Th2-associated lung inflammation, in particular through its expression by dendritic cells, has been well characterized (Schuijs et al, 2015;Vroman et al, 2018). On the other hand, some cases of A20 haploinsufficiency yield distinct autoinflammatory and/or autoimmune skin pathology, possibly with skin ulcerations and pustular abscesses (Kadowaki et al, 2017;Takagi et al, 2017;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Keratinocyte-specific deletion of A20 results in epidermal hyperproliferation and ectodermal defects, but skin infiltration of immune cells has not been observed (Lippens et al, 2011). Genome-wide association studies identified TNFAIP3/A20 as a susceptibility locus for psoriasis (Haase et al, 2015;Indhumathi et al, 2015;Li et al, 2014;Nair et al, 2009;and Zhang et al, 2015), and its role as a negative regulator in Th2-associated lung inflammation, in particular through its expression by dendritic cells, has been well characterized (Schuijs et al, 2015;Vroman et al, 2018). On the other hand, some cases of A20 haploinsufficiency yield distinct autoinflammatory and/or autoimmune skin pathology, possibly with skin ulcerations and pustular abscesses (Kadowaki et al, 2017;Takagi et al, 2017;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Several publications have appeared to identify the TNFAIP3 gene as a susceptibility locus for the human autoimmune pathology. [8,9,15,2628] The TNFAIP3 gene is also regarded to closely associate with the autoimmune diseases. However, for the 2 SNPs in the present study, such an association of TNFAIP3 gene with the MG subjects was observed only in the LOMG.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed in UK 19 , Egypt 20 , India 21 , China [22][23][24][25] , Pakistani 26 , USA 27 , Sweden 28 , México 29 . In all, these studies included 11,556 psoriasis patients and 16,720 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%